The effect of location and indole butyric acid (IBA) on rooting stem cuttings of Dog rose (Rosa canina) - سعيد , عمار; عماد قبيلي; ناديا صفوت (Latakia University Journal -Biological Sciences Series, 2025)
The experiment was carried out in the Tishreen agricultural nursery of the Directorate of Agriculture in Latakia (Bouqa) within a special greenhouse. cuttings from the wild Dog roses spread in two locations in Jableh rural, Latakia, Syria: Bsheli and Helbako. Cuttings was treated with three Concentrations of indole butyric acid: 0, 1000 and 5000 ppm. The experiment was designed as a factorial experiment with two factors: location and hormone concentration. The results showed that the rooting ability of semi-hardwood cuttings varies depending on the location and hormone concentration. It was shown that the cuttings taken from Bsheli was superior to the Helbako location. The best hormone concentration to obtain the highest rooting rate and the best survival rate was 1000 ppm of indole butyric acid. It was found that there was a significant interaction between location and hormone concentration in its effect on the percentage of rooting, root length and number, and survival rate. We recommend using indole butyric acid at a concentration of 1000 ppm for rooting steem cuttings of Dog rose.